Planning and implementation of a FIGO postpartum intrauterine device initiative in six countries. (18th September 2018) - de Caestecker, Linda; Banks, Laura; Bell, Eliza; Sethi, Maya; Arulkumaran, Sabaratnam
Abstract: Objective: To describe the process of planning and implementing a program of counselling and delivery of postpartum intrauterine devices (PPIUD) in 48 hospitals across six countries in Africa and Asia. Methods: The process of planning the FIGO PPIUD initiative, selection of countries and hospitals, model of implementation, and lessons for the future are described. Results: Country‐level and hospital‐based leadership were essential and training‐the‐trainer models were successful. There was a need for consistency of competency standards allowing for national variations. As the project progressed, additional steps were necessary for steady implementation of the initiative, specifically: establishment of a project steering committee and a data safety monitoring committee, audits of structure and process, and regular feedback of each center's performance to stimulate maintenance and enhancement of activities. Postnatal follow‐up was challenging in many countries with fragmented maternity systems. Conclusion: The importance of professional leadership and commitment backed by robust data for monitoring and feedback are essential for success. Abstract : Planning and implementation of a FIGO initiative to provide immediate postpartum intrauterine device (PPIUD) contraception for birth spacing in six countries is described.